2017
DOI: 10.1188/17.cjon.699-709
|View full text |Cite
|
Sign up to set email alerts
|

MAPK Pathway–Targeted Therapies: Care and Management of Unique Toxicities in Patients With Advanced Melanoma

Abstract: The key AEs associated with these agents included pyrexia and cutaneous toxicities. Other notable AEs included arthralgias, ocular toxicities, and cardiac events. Because these agents are administered until progressive disease or unacceptable toxicity, nurses should be aware of management strategies to optimize treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The grey square corresponds to patients who received cardiotropic treatments, whereas the grey circle represents patients who did not of BRAF and MEKis. [8][9][10] In the present study, 3 patients (3.4%) presented a decline in LVEF ≥10% to a value <50% (data not shown). This frequency is consistent with that reported in clinical trials.…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations
“…The grey square corresponds to patients who received cardiotropic treatments, whereas the grey circle represents patients who did not of BRAF and MEKis. [8][9][10] In the present study, 3 patients (3.4%) presented a decline in LVEF ≥10% to a value <50% (data not shown). This frequency is consistent with that reported in clinical trials.…”
Section: Discussionmentioning
confidence: 39%
“…No patient was treated with the combination of encorafenib-binimetinib. The median duration of treatment was 9 months (IQR [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]). 30 patients (34.1%) had a rechallenge after progressive disease under previous treatment with BRAF and/or MEKis.…”
Section: Baseline Characteristics Of Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo studies in mice have demonstrated that a disruption of certain growth factors inputs, including those of VEGF and fibroblast growth factors (FGFs), results in reduction of ERK signaling and the loss of vascular integrity and vessel involution ( Lee et al, 2007 ; Murakami et al, 2008 ). At the same time, clinical uses of drugs targeting VEGF, such as bevacizumab, or the downstream signaling pathway, such as the mitogen-activated kinase (MEK) inhibitor trametinib, are associated with extensive and poorly understood cardiovascular side effects, including hemorrhage and hypertension ( Porta et al, 2015 ; Banks et al, 2017 ; Rubin, 2017 ). These observations notwithstanding, the role of ERK signaling and specific ERK isoforms in these events is unknown.…”
Section: Introductionmentioning
confidence: 99%